The impact of natural disturbance dynamics on lichen diversity and composition in primary mountain spruce forests. (25th October 2021) - Langbehn, Thomas; Hofmeister, Jeňýk; Svitok, Marek; Mikoláš, Martin; Matula, Radim; Halda, Josef; Svobodová, Kristýna; Pouska, Václav; Kameniar, Ondrej; Kozák, Daniel; Janda, Pavel; Čada, Vojtěch; et al.
Abstract: Aim: Natural disturbances influence forest structure, successional dynamics and consequently, the distribution of species through time and space. We quantified the long‐term impacts of natural disturbances on lichen species richness and composition in primary mountain forests, with a particular focus on the occurrence of endangered species. Location: Ten primary mountain spruce forest stands across five mountain chains of the Western Carpathians, a European hotspot of biodiversity. Methods: Living trees, snags and downed logs were surveyed for epiphytic and epixylic lichens in 57 plots. Using reconstructed disturbance history, we tested how lichen species richness and composition was affected by the current forest structure and disturbance regimes in the past 250 years. We also examined differences in community composition among discrete microhabitats. Results: Dead standing trees as biological legacies of natural disturbances promoted lichen species richness and the occurrence of threatened species at the plot scale, suggesting improved growing conditions for rare and common lichens during the early stages of recovery post disturbance. However, high‐severity disturbances compromised plot‐scale species richness. Both species richness and the number of old‐growth specialists increased with time since disturbance (i.e., long‐term uninterrupted succession). No lichen species was strictly dependent on live trees as a habitat, but numerous species showed specificity to logs, standing objects or an admixture of tree species. Conclusions: Lichen species richness was lower in regenerating, young and uniform plots compared with overmature and recently disturbed areas. Natural forest dynamics and its legacies are critical to the diversity and species composition of lichens. Spatio‐temporal consequences of natural dynamics require a sufficient area of protected forests for provisioning continual habitat variability at the landscape scale. Ongoing climatic changes may further accentuate this necessity. Hence, we highlighted the need to protect the last remaining primary forests to ensure the survival of regionally unique species pools of lichens. Abstract : We documented that natural forest dynamics and its legacies are critical to the diversity and species composition of lichens in primary spruce mountain forests. Both species richness and the number of old‐growth specialists increased with time since disturbance. Spatio‐temporal consequences of natural dynamics require a sufficient area of protected forests for provisioning continual habitat variability at the landscape scale.